Sorção de fósforo em cinco solos do estado de Minas Gerais: influência de alguns fatores - Batista de Faria, Clementino Marcos; Braga, José Mário; Cristo Brumano Pinto, Onofre (Revista Ceres, 2025)
The objective of this work was to study the influence of some factors on the sorption of phosphorus in five Dark Red Latosols having different physical and chemical characteristics, especially in relation to the buffer capacity of phosphorus.